2021
DOI: 10.47275/2692-0948-121
|View full text |Cite
|
Sign up to set email alerts
|

The Intricate Interactions between Maternal Smoking and Drinking During Pregnancy and Birthweight Z-Scores of Preterm Births

Abstract: Background:The extent to which smoking and drinking in a local community is associated with nutrition and Z-scores of infants from spontaneous preterm deliveries, is uncertain. Aim:To investigate associations of different levels of maternal smoking and drinking in spontaneous preterm birth with infant birthweight Z-scores.Methods: Information, including gestational age (determined by earliest ultrasound), maternal arm circumference (measured at enrolment), smoking-drinking data (obtained up to 4 occasions), bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
(45 reference statements)
3
6
0
Order By: Relevance
“…There was no significant difference between the Control and NoDrugsDrinkSmoke, MarDrink or MarDrinkSmoke groups. Our previous study also found that alcohol use alone was associated with a higher GA, while alcohol seemed to counteract the negative association of smoking with GA, [26] and Gestational age at enrolment differed significantly between any two groups when there was no overlap of letters above the vertical bars.…”
Section: Birth Outcomes and Trendsmentioning
confidence: 61%
See 4 more Smart Citations
“…There was no significant difference between the Control and NoDrugsDrinkSmoke, MarDrink or MarDrinkSmoke groups. Our previous study also found that alcohol use alone was associated with a higher GA, while alcohol seemed to counteract the negative association of smoking with GA, [26] and Gestational age at enrolment differed significantly between any two groups when there was no overlap of letters above the vertical bars.…”
Section: Birth Outcomes and Trendsmentioning
confidence: 61%
“…Our finding that women who smoked, whether combined with drugs and/or alcohol or not, had significantly smaller MUACs, has been confirmed by two previous studies. [ 26 , 35 ] The reduced MUAC, associated with cigarette smoking and indicating poorer nutritional status, was associated with an increased risk of spontaneous preterm birth as well as a lower infant BWZ. [ 26 , 35 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations